An Empirical Investigation of Budget and Trade Deficits: The Case of Bangladesh - ., Asrafuzzaman; Roy, Amit; Gupta, Sanat Das (International Journal of Economics and Financial Issues, 2013)
This study attempts to investigate the evidence of twin deficits hypothesis, that is, the simultaneous existence of fiscal and foreign trade account deficits in Bangladesh. In this regard this paper examines the causal relationship between budget deficit and trade deficit based on annual time series data from 1972-73 to 2011-12 fiscal year. Applying the VAR and Granger Causality after successfully running ADF and PP unit root test and cointegration rank test this paper reveals that budget deficit Granger cause trade deficit and vice versa but the relationship does not stand for the long-run dynamics. In fact, the long run relationship depends on overall macroeconomic environment and performances of other relevant variables. Policy implication is that Government should reduce budget deficit to improve the trade account balance. Keywords: Twin deficits; Bangladesh; Budget deficit; Trade deficit; Granger causality; VAR JEL Classifications: F11; F32; F41; H62